METHODS FOR VEGETATIVE REPRODUCTION OF SOME BEAUTIFUL TREES AND SHRUBS (British Journal of Global Ecology and Sustainable Development, 2023)
In the article Chitalpa tashkentensis T.S. Elias & Wisura, Melia azedarach L., and Rhus coriaria L., methods of reproduction from vegetative organs have been researched. Also, the methods of reproduction of plants, planting periods, the height of annual branches, the diameter of the root neck, swelling, the preservation of seedlings, and the importance of using seedlings in landscaping were discussed.